Formation of SiHx on Silicon (100) using low energy negative hydrogen ions from a magnetized sheet plasma source - Fernandez, Marcedon S. (2004)
Common to methods of preparation of hydrogenated silicon (a-Si:H) and polycrystalline silicon silicon films done in the plasma done in plaza Enhanced Chemical Vapor deposition (PECVD) and other deposition experiments is the lack of explanation to the mechanism of deposition. This inadequacy deters to enlighten the problem why optical, electronic and electrical property transitions take place after the introduction of hydrogen in Silicon sustrates. Silicon hydrides (SiHx) have been studied carefully as they continue to be prominent materials in microelectronic device manufacturing. They are suitred for numerous applications including photovoltaics and thin film transistors (TFTs. The results of this work attempt to make fiew contributions to the bulk of physical explanations of hydrogeneration effects on Si substrate. In this study, ion deposition is employed. Unlike most of the various researches illustrating ion-surface interaction that had utilized positive ions, negative hydrogen ions (<100eV energy) of current flux -0.26 A/m2 extracted from a magnetized sheet plasma negative ion source are studied using a drift-rectangular parallelepiped with two electrodes. This functions like a mass analyzer defelecting undesired charged particles allowing only the passage of H ions under specific conditions of biasing of electrodes. The energies of the segregated negative hydrogen ions are controlled to desired hyperthermal range.